Volume of public finances as a subject of control - Хмельков, Андрій Володимирович; Khmelkov, Andrii V. (Харківський навчально-науковий інститут ДВНЗ «Університет банківської справи», Харків, Україна, 2019)
The method proposed in the article to accurately calculate the amount of public finances as a subject of control makes it possible to satisfy the socio-economic need in the definition of value of control subject. The main focus of the research is to identify an improved analytical indicator for calculating the value of public finances PFR* (formula (1)), which is more versatile and absolute indicator. The proposed improvements are to take into account the elements of purely financial origin, namely: Consolidated Budget and Single Country Contribution. Such composition of the improved indicator overcomes the flaw of the existing formula, where the elements are the institutions that make up the state social insurance system and have an unstable and volatile nature. This, in turn, allowed developing a number of formulas that were confirmed by the made calculations, in particular: formulas of the volume of control subject for the corresponding reporting period (according to the planned aggregate value of public finances of the country) (formulas (2), (3)); the formula of the volume of control subject for the relevant reporting period (as a cumulative indicator of the cost expression of the country’s public finances upon execution) (formula (4)); the formula of absolute damage to the subject of control (for the relevant reporting period) (formula (5)); the formula for calculating a parameter for an effective and highly efficient institute of counrty control (formula (6)). The obtained indicators PFR*, TSCPFY, TSCPFY*, ALTSCPFY* made it possible to analyze supervisory reviews undertaken by the agents of the national institute of control and work out the parameter of quality assurance and quality assessment of the national institute of control. According to these test results, the developed indicators proved to be the tools of theoretical and practical scientific research of the institute of control as one of the elements of the institutional infrastructure of public finances, which directly ensures their stability.
Обсяг публічних фінансів як предмет контролю
Запропонований спосіб точного обчислення обсягу публічних фінансів як предмета контролю дає змогу задовольнити суспільно-економічну потребу у визначенні вартісного вираження предмета контролю. В основному фокусі дослідження – визначення удосконаленого аналітичного показника розрахунку вартісного вираження публічних фінансів – PFR*, який є більш універсальним та удосконаленим показником. Запропоновані удосконалення полягають в урахуванні елементів, які мають виключно фінансове походження, а саме: Зведеного бюджету та Єдиного внеску країни. Такий склад уточненого показника долає недосконалість формули, що вже існує, де елементами є інституції, що становлять систему державного соціального страхування та мають неусталений і мінливий характер. Це, у свою чергу, дало змогу розробити низку формул, які знайшли підтвердження проведеними розрахунками, зокрема: формули обсягу предмета контролю за відповідний звітній період (за плановим сукупним показником вартісного виразу публічних фінансів країни) (формули (2), (3)); формула обсягу предмета контролю за відповідний звітній період (як сукупний показник вартісного вираження публічних фінансів країни за фактом виконання) (формула (4)); формула абсолютного збитку нанесеного предмета контролю (за відповідний звітній період) (формула (5)); формула формулюванням параметра для дієвого та високоефективного інституту контролю країни (формула (6)). Отримані показники PFR*, TSCPFY, TSCPFY*, ALTSCPFY* дозволили здійснити аналіз проведення контрольних дій агентами інституту контролю країни та дали змогу сформулювати параметр забезпечення та визначення якості інституту контролю країни. За результатом власної апробації розроблені показники довели, що вони є інструментами наукового пошуку в теоретичній і практичній площині у сфері інституту контролю як одного з елементів інституційної інфраструктури публічних фінансів, що безпосередньо забезпечує їхню стабільність.
Keywords: value terms of public finances; institutional infrastructure; institute of control; agents of the institute of control; the subject of the control institute; public finance; stability of public finances